The Importance of Cancer Stem Cells and Their Pathways in Endometrial Cancer: A Narrative Review - Laura Georgiana Caravia; Melinda Ildiko Mitranovici; Ioan Emilian Oala; Andreea Taisia Tiron; Anca Angela Simionescu; Alina Maria Borcan; Marius Craina (Cells)
Endometrial cancer is one of the most common malignancies seen in women in developed countries. While patients in the early stages of this cancer show better responses to surgery, adjuvant hormonal therapy, and chemotherapy, patients with recurrence show treatment resistance. Researchers have recently focused on cancer stem cells (CSCs) in the treatment of gynecologic cancer in general but also specifically in endometrial cancer. CSCs have been investigated because of their resistance to conventional therapies, such as chemo- and radiotherapy, and their ability to induce the progression and recurrence of malignancy. The activation of alternative pathways, such as WNT, PI3K, NF-kB, or NOTCH, could be the basis of the acquisition of these abilities of CSCs. Their specific markers and signaling pathways could be treatment targets for CSCs. In this article, we discuss the importance of obtaining a better understanding of the molecular basis and pathways of CSCs in endometrial cancer and the role of CSCs, aiming to discover more specific therapeutic approaches.